PENCEGAHAN KERUSAKAN BAHAN PUSTAKA KERTAS (PREVENTIVE PRESERVATION) MELALUI METODE SURVEI KONDISI FISIK KOLEKSI PADA PERPUSTAKAAN UNIVERSITAS SARI MUTIARA - Nisa Khalish; Ananda Aprilia; Rizki Rahmawati; Alya Rahmayani; Daffa Ananda Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Preventive preservation is a series of actions aimed at maintaining and extending the usability of library materials by preventing potential damage before it occurs. This study aims to analyze preventive preservation efforts at the University of Sari Mutiara Indonesia Library through the implementation of a physical condition survey of printed collections. The research employed a descriptive qualitative method with data collected through interviews, observation, and documentation. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings show that the library has carried out several preventive preservation practices such as book covering, manual rebinding, routine light cleaning, environmental control, temperature and lighting regulation, pest prevention, and enforcing user regulations. The physical condition survey proved effective in identifying both minor and major damages, determining repair priorities, and formulating data-based preservation plans. The survey also helped the library detect trends in collection damage and determine the need for additional tools or human resources. However, preservation efforts are still constrained by limited staff, inadequate funding, and insufficient preservation equipment. Thus, although preventive measures are implemented, they have not yet reached optimal performance due to institutional and resource limitations.